Harnessing Plant Biodiversity for the Discovery of Novel Anticancer Drugs Targeting Microtubules - Xie, Songbo; Zhou, Jun (Frontiers in Plant Science, 2017)
The microtubule cytoskeleton plays a critical role in a wide range of cellular activities and has been shown to be a highly effective target for the treatment of human malignancies. Despite the recent focus on proteomics and high-throughput profiling, it is clear that analysis of plant extracts has yielded several highly efficacious microtubule-targeting agents (MTAs) currently in clinical use, as well as agents in the current pipeline with promising efficacy. To date, a large proportion of the world’s plant biodiversity remains untapped by the pharmaceutical industry, presenting a major opportunity for the discovery of novel pharmacologically-active lead compounds. Because plants contain an astonishing array of structurally diverse molecules, they represent an ideal source for the discovery of novel MTA leads. To demonstrate the importance of searching for novel bioactive compounds across the plant kingdom, herein, we summarize the discovery and development of plant-derived MTAs and discuss the challenges associated with searching for novel bioactive compounds from plants. We propose potential solutions to these problems with the aim of facilitating further exploration and identification of novel MTAs from plant biodiversity.